Relationship strength characterized by accuracy and fast speed motor for handling in football - Nagi, Deyaa (Journal of Physical Education, 2009)
The Knowledge of The Type of Relationship Between The Physical Abilities and Skills Will helps The Coaches to identifiy the terms of the training course and load components according to his Scientific information, The aims of Research are: • Know The Relation of Power and Movement Speed and Accuracy in Football. • The Subject of the Study Consist of (10) player Representing The Youth League. • There is a week Relation Between the power, Accuracy and movement speed for Passing. • The Player Whom has power not necessary to nave the Accuracy and Movement Speed for Passing